3DOM SiO2‐Supported Different Alkali Metals‐Modified MnOx Catalysts: Preparation and Catalytic Performance for Soot combustion. Issue 31 (6th November 2017) - Yu, Xuehua; Wang, Lanyi; Zhao, Zhen; Fan, Xiaoqiang; Chen, Maozhong; Wei, Yuechang; Liu, Jian
Abstract: A series of novel and cheap catalysts, which contain three‐dimensionally ordered macroporous (3DOM) structure and alkali‐doped MnOx nanoparticles, were designed and prepared by a facile method. The physical and chemical properties of as‐prepared catalysts were characterized by XRD, SEM, TEM, Raman and H2 ‐TPR and so on. The as‐prepared catalysts exhibit excellent catalytic performance for soot combustion, which the T10, T50 and T90 are 275 o C, 323 o C and 351 o C, respectively. This activity result is comparable to or even higher than noble metal catalyst in the medium and high temperature range. The high catalytic activities of as‐prepared catalysts are attributed to marcroporous structure, nano‐effect, immobilization effect and synergistic effect. Based on the analysis results, the possible reaction mechanisms of catalysts for soot combustion, were also proposed. Due to easy synthesis, low cost, high activity, the as‐prepared catalysts are promising for practical applications, and this work also provides potential research approaches to get excellent catalysts. Abstract : A series of 3DOM SiO2 ‐supported different alkali metals‐modified MnOx catalysts were designed and prepared by a facile method, and they exhibit excellent catalytic performance for soot combustion. Four important factors, which include marcroporous structure, nano‐effect, immobilization effect and synergistic effect, are beneficial to super catalytic performance of as‐prepared catalysts.